2015
DOI: 10.17148/iarjset.2015.21202
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Barriers and Productive Zones Using Reservoir Characterization

Abstract: Abstract:The most common complication faced by petroleum engineers is the description of a reservoir, both accurately and efficiently. Inadequate and insufficient reservoir characterization lead most enhanced oil recovery and secondary recovery projects to fail and also makes it difficult to deal with heterogonous reservoir. An accurate description of a reservoir is vital to the reservoir management and achieving maximum oil recovery. Reservoir characterization plays a very important role in descripting the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Assessing the environmental impact especially in green projects is a necessary to build a common ground for competition with other alternatives in a growing sustainable green economy offering a plethora of alternatives and options. Due to ammonia being one of the most produced chemicals worldwide with already established facilities, [41][42][43] assessing the direct impacts like the resources consumption from water, energy and materials is already acknowledged. Although the process is green, analyzing the potential of any indirect pollutants and greenhouse gases (GHG) [44][45][46].…”
Section: Environmental Impact Assessmentmentioning
confidence: 99%
“…Assessing the environmental impact especially in green projects is a necessary to build a common ground for competition with other alternatives in a growing sustainable green economy offering a plethora of alternatives and options. Due to ammonia being one of the most produced chemicals worldwide with already established facilities, [41][42][43] assessing the direct impacts like the resources consumption from water, energy and materials is already acknowledged. Although the process is green, analyzing the potential of any indirect pollutants and greenhouse gases (GHG) [44][45][46].…”
Section: Environmental Impact Assessmentmentioning
confidence: 99%
“…Enhanced oil recovery (EOR) techniques are utilized to increase the recovery of oil even further . Accurately predicting water saturation and areal sweep efficiency, along with conducting thorough reservoir characterization, is crucial for the success of enhanced oil recovery techniques, as they have the potential to increase production rates and ultimately improve oil recovery rates. EOR techniques encompass chemical flooding, which involves the utilization of polymers, surfactants, alkalis, or a combination of these chemicals, gas flooding, which utilizes carbon dioxide, , and thermal injection that involves the application of steam or in situ combustion. Alkalis and surfactants are commonly utilized in chemical-based oil recovery techniques to enhance both the microscopic and macroscopic sweep efficiency of oil. , …”
Section: Introductionmentioning
confidence: 99%
“…In the Venezuelan Eocene, permeability was accurately predicted, and the hydraulic flow unit (HFU) was determined on sandstone reservoir rock. Attia et al 36 demonstrated that reservoir characterization is critical for secondary and enhanced oil recovery projects. The main goal of the research was to use reservoir characterization to identify productive zones and the barriers of the reservoir.…”
Section: Introductionmentioning
confidence: 99%